Sobre as tensões simbólicas da economia solidária : reconstruindo a biografia de um administrador do banco de tempo de Porto Alegre - Pinheiro, João Pedro Martins (2022)
In this interpretive social research, I investigate the concrete experience of a solidarity economy system called time bank (TB). It is usually a service exchange club where users carry out transactions using a currency that can only be used within the TB system, called credit-hour. One hour of service costs one credit-hour. In general, administrators are required to manage the member account balances and the transactions between members. Employing Gabriele Rosenthal’s biographical narrative method, I analyze the biography of Antônio, an administrator of TB Porto Alegre, RS (TB-POA), which was active between 2017 and 2019 through a Facebook group. The analysis identified the interpretive processes and the pattern of conduct that the research participant developed throughout his life trajectory and that influenced his experience of the BDT-POA. More specifically, based on the biographical narrative interview I conducted with Antônio in August 2021 and on the data I was able to collect from the internet (mainly from social networks), I identified a role of reconciler in him that was fundamental to understand his subjective experience as a TB-POA administrator. Moreover, it became clear that the type of “ambitious centralizing administrator”, as I called him, that Antônio became was the result of a process of social construction that dates back to his childhood and that stifled other, less ambitious, visions for the TB-POA, that could have resulted in a more enduring organization. The reasons why are discussed. In the conclusion, I recommend that TBs should start with a small but dedicated group, where the administrative responsibility is shared by all or nearly all and where there is a consensus among these founding members regarding everyone's expectations for the TB